2018
DOI: 10.1186/s41512-018-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for independent external validation of cardiovascular risk clinical prediction rules: Cox proportional hazards regression analyses

Abstract: Background: Clinical prediction rules (CPRs) should be externally validated by independent researchers. Although there are many cardiovascular CPRs, most have not been externally validated. It is not known why some CPRs are externally validated by independent researchers and others are not. Methods: We analyzed cardiovascular risk CPRs included in a systematic review. Independent external validations were identified by forward citation searches of derivation studies. Time between the publication of a cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The selected prognostic model was calibrated well (Figure A.1 in supporting information) and the observed median disease duration was well captured by the predicted median disease duration (Figure A.2 in supporting information). The baseline survival (information that is necessary for calculating individual risk 28 ) was 99.6% at 1 month. A score chart was derived to predict 6‐month survival and median disease duration based on the selected model (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The selected prognostic model was calibrated well (Figure A.1 in supporting information) and the observed median disease duration was well captured by the predicted median disease duration (Figure A.2 in supporting information). The baseline survival (information that is necessary for calculating individual risk 28 ) was 99.6% at 1 month. A score chart was derived to predict 6‐month survival and median disease duration based on the selected model (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Other types of external validation studies include methodologic validation which refers to testing using data collected via different methods, spectrum validation which refers to testing in patients with different disease severity or prevalence of the outcome of interest and fully independent validation which refers to testing by independent investigators at different sites [26, 147]. A recent study of cardiovascular risk CPRs found that very few were externally validated by independent researchers; to increase the chance of fully independent validation, researchers should report all the information required for risk calculation, to ensure replicability [178]. Some authors have found that CPRs demonstrate worse performance in fully independent external validation studies compared to temporal or geographical external validation studies [26, 28], while others have found no difference [179].…”
Section: Stages In the Development Of Clinical Prediction Rulesmentioning
confidence: 99%
“…More updating studies are required. External validation studies evaluating the transportability of a risk equation to a new population are still not common; e.g., in a recent systematic review, Ban et al found that only 23% of 125 CVD equations were externally validated 32 . Updating studies combining evidence from published equations with new data to tailor the prediction tool to other populations or to update them because of changes over time are even rarer.…”
Section: Discussionmentioning
confidence: 99%